Patients' Perspectives on Transforming Clinical Trial Participation: Large Online Vignette-based Survey - Van Thu Nguyen; Philippe Ravaud; Viet Thi Tran; Bridget Young; Isabelle Boutron (JMIR Publications, 2022)
BackgroundPatients' participation is crucial to the success of randomized controlled trials (RCTs). However, recruiting and retaining patients in trials remain a challenge. ObjectiveThis study aims to describe patients' preferences for the organization of RCTs (visits on- site or remotely) and evaluate the potential impact of fulfilling preferences on their willingness to participate in a clinical trial. MethodsThis was a vignette-based survey. Vignettes were case scenarios of real clinical trials assessing pharmacological treatments. These RCTs evaluated 6 prevalent chronic diseases (ie, osteoporosis, osteoarthritis, asthma, cardiovascular diseases, diabetes, and endometriosis). Each vignette described (1) the RCT and characteristics of the treatment tested (ie, doses, administration routes) and (2) the trial procedures and different options (on-site or remotely) for how the trial was organized for informed consent, follow-up visits, and communication of results when the trial was completed. We recruited 628 participants from ComPaRe (www.compare.aphp.fr), a French e-cohort of patients with chronic diseases. The outcomes were the participants' preferences for the way the trial was organized (on-site or remotely) and their willingness to participate in the trial. ResultsOf the 628 participants who answered the vignettes, 491 (78.2%) were female (median age 55 years), with different chronic diseases ranging from endometriosis in 59 of 491 (12%) patients to asthma in 133 of 628 (21.2%) patients. In addition, 38 (6.1%) participants wanted to provide informed consent and all trial visits on-site, 176 (28%) wished to participate in the trial entirely remotely, and 414 (65.9%) wanted to combine remote-based and hospital-based visits. Considering the trial as a whole, when the trial was organized in a way that the patients preferred, the median (Q1-Q3) likelihood of participation in the trial was 90% (80-100) versus 60% (30-80) if the trial followed the patients' nonpreferred model. Furthermore, 256 (40.8%) patients responded to open-ended questions expressing their experience with trial participation and visits to the hospital and providing suggestions for improvement. The patients emphasized the need to personalize the way a trial is organized according to each patient's needs and conditions. ConclusionsThere was a significant diversity in the participants' preferences. Most participants preferred hybrid organization involving both on-site and remote visits. Participants were more likely to participate in a trial organized according to their preferences.